Compositional variation of clinopyroxenes of basaltic, essexitic and tephriphonolitic rocks from the Doupovske hory Volcanic Complex, NW Bohemia - Rapprich,V. (Journal of the Czech Geological Society, 2005)
Variation of chemical composition of clinopyroxenes in basaltic volcanic rocks, including lavas and shallow intrusions of the Doupovske hory Volcanic Complex, was studied. High Ca (mostly over 90% of M2 site) and Mg contents of analyzed clinopyroxenes qualify them as diopsides. With respect to Al and Ti admixtures, full name of titanian aluminian diopside should be used in most cases. The name augite, traditionally used in older literature without support by analytical data, is no more applicable. During crystallization of basaltic rocks, the composition of clinopyroxenes changed to Fe-rich diopside in phenocryst rims and mitrix microcrysts. The contents of Al, Ti and Fe increased from cores to rims, whereas Si and Mg decreased. The same compositional shifts were observed in clinopyroxenes of essexitic rock. Record of compositional changes is documented in zoned clinopyroxene phenocrysts from tephriphonolite. Cores of these phenocrysts show composition similar to clinopyroxenes in basaltic rocks, whereas their rims are of sodian aluminian diopsidic composition differing significantly in higher Fe/Mg and Na/Ca ratios and a low Ti content.
Keywords: Clinopyroxene; diopside; mineral chemistry; Doupovske hory Mts.; basalts; essexite; tephriphonolite